اسلاموفوبیا کے بنیادی محرکات: تجزیہ و تدارک: The Root Causes of Islamophobia: Analysis and Remedies - Hussain, Dr.Mubasher; Akhtar, Dr.Jamil (MEI, 2023)
The history of the interaction between Islam and the “others,” particularly the West--- that is spread over the span of fourteen centuries--- is full of surprises ranging from learning, peace, alliance and co-existence to hate, controversies and war and beyond. Hence, both the ends took advantages to understand each other but unfortunately the dark side of this interaction has been visible on many occasions because of certain reasons including the stereotypes associated with Islam. The history of the Crusades might be a relevant example in this context, which allows the observers to better understand the various factors behind the conflict between Islam and the West. Some people in the West, relying upon the prevailing stereotypes, consider Islam as a religion of violence and extremism that intends to forcefully "Islamize" the Western world. On the other hand, there are some circles in the Islamic world that believe in the similar stereotypes associated with the West and its civilization. This paper attempts to identify the various domestic and international trajectories of Islamophobia---for the attention of policy makers and think tanks---in order to address them from the Islamic religious perspective with the aim to bring about a constructive change to the socio-religious outlook of the hardliners of each end.